Implementasi Program Kredit Kukar Idaman dalam Pengembangan UMKM di Kabupaten Kutai Kartanegara - Zihan Fahdila, Andi; Reza Fahlevy, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study aims to determine and describe the implementation of the Kukar Idaman Credit Program in Kutai Kartanegara Kec. Tenggarong. The definition and requirements of Micro, Small and Medium Enterprises (MSMEs) are stipulated in Law Number 20 of 2008, The focus of this research on the implementation of a credit program is applied to the program. The data collection technique used is purposive sampling. The results of this study indicate that the implementation of the Kukar Idaman Credit Program in Kutai Kartanegara kec. Tenggarong. This program has been running from 2021 to 2024 for 3 years, then the program's supporting factors facilitate the economic growth of MSMEs, encourage consumers to influence targets in the economy, manage risk and liquidity to enable individuals to manage the risks that occur. The inhibiting factor is that the Kukar Idaman Credit Program has not been able to reach remote areas in the Kutai Kartanegara Regency area.